ANALISIS PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP TAX AVOIDANCE DENGAN DIMODERASI GOOD CORPORATE GOVERNANCE - Levi Martantina; R. Soerjatno (Jurnal Bisnis Terapan, 2018)
This study aims to examine the effect of Corporate Social Responsibility on Tax Avoidance in which Good Corporate Governance is moderating variable. Corporate Social Responsibility is independent variable whereas dependent variable is Tax Avoidance. The result of testing the first hyphothesis found that Corporate Social Responsibility has a negative effect on Tax Avoidance. In other words, the company that does extensive disclosure, the company does not practice Tax Avoidance. The result of testing the second hypothesis found that the exixtence of Good Corporate Governance in the board of directors mediate the influence of Corporate Social Responsibility with Tax Avoidance. So that the existence of the board of directors is able to contribute in making extensive disclosure towards Corporate Social Responsibility and practice of Tax Avoidance.